Background exposure to polychlorinated biphenyls and all-cause, cancer-specific, and cardiovascular-specific mortality: A systematic review and meta-analysis. (September 2021) - Fiolet, Thibault; Mahamat-Saleh, Yahya; Frenoy, Pauline; Kvaskoff, Marina; Romana Mancini, Francesca
Highlights: Evidence of the impact of background exposure to polychlorinated biphenyls (PCBs) on all-cause mortality is limited. Dietary exposure to PCBs is associated with an increased risk of cardiovascular-specific mortality. Studies assessing PCB exposure in the general population are lacking. Abstract: Background: Polychlorinated biphenyls (PCBs) are a large family of man-made organic, ubiquitous, and persistent contaminants with endocrine-disrupting properties. PCBs have been associated with numerous adverse health effects and were classified as carcinogenic to humans, but their long-term impact on mortality risk in the general population is unknown. Objective: To conduct a systematic review and meta-analysis in order to assess whether background exposure levels of PCBs increase all-cause and cancer- and cardiovascular-specific mortality risk in the general population. Methods: We searched the Pubmed, Web of Science, Cochrane Library, and Embase databases for eligible studies up to 1st of January, 2021. We included cohort and nested-case control studies comparing the lowest vs. the highest background exposure level of PCBs in the general population and reporting data for all-cause mortality and/or cancer-/cardiovascular-specific mortality. Studies reporting occupational and accidental exposures were excluded. Random-effects meta-analysis was used to estimate summary relative risks (SRRs) and 95% confidence intervals (CIs). Heterogeneity across studies was assessed by I2 statistics, and publication bias both graphically and using Egger's and Begg's tests. Quality of included studies was assessed using the National Toxicology Program/Office of Health Assessment and Translation (NTP/OHAT). Confidence in the body of evidence and related level of evidence were assessed using the Grading of Recommendations Assessment, Development and Evaluation (GRADE) based on the NTP/OHAT framework. The protocol was registered in PROSPERO (CRD42020178079). Results: The initial search led to 2, 132 articles. Eight prospective cohort studies met our inclusion criteria, leading to 72, 852 participants including 17, 805 deaths. Overall exposure to PCBs was not statistically significantly associated with all-cause mortality (SRR = 1.13, 95% CI = 0.90–1.41, n = 7 studies, low certainty); however, dietary exposure to PCBs was associated with an increased risk of cardiovascular-specific mortality (SRR = 1.38, 95% CI = 1.14–1.66, n = 3 studies, moderate certainty), while no association was found with cancer-specific mortality (SRR = 1.07, 95% CI = 0.72–1.59, n = 5 studies, low certainty). Conclusion: Our meta-analysis suggests that background exposure to PCBs is associated with an increased risk of cardiovascular-specific mortality in the general population with a "moderate" level of evidence. These findings should be interpreted with caution given the small number of studies on mortality in the general population.